Child Identity Card (KIA) Manufacturing Services at DISDUKCAPIL Lahat to Increase Public Awareness: Pelayanan Pembuatan Kartu Identitas Anak (KIA) di DISDUKCAPIL Lahat Guna Meningkatkan Kesadaran Masyarakat - Komala Sari, Dina; Amaludin, Amaludin; Fitriadi, Heri (Gayaku Publisher, 2023)
This research was conducted as an effort to realize the quality of public services at the Population and Civil Registration Service (DISDUKCAPIL) of Lahat Regency and the community towards orderly Population Administration in order to create public awareness in making KIA (Child Identity Cards). The method used in this research uses a qualitative descriptive method. This research aims to understand, examine and describe the results of research findings regarding the quality of KIA services at the Lahat Regency Population and Civil Registration Service. In service practice, the skills and credibility of employees in responding to public complaints are quite good. The established service procedures are easy to understand and not complicated. However, several facilities, infrastructure and information required are not adequate and meet good service standards as well as information media regarding the requirements for submitting KIA and Population Documents by the community in order to simplify the process of creating population documents in order to improve the quality of service and community satisfaction. The quality of service based on research is quite good and the public is aware that they must have KIA according to the child's domicile, the service is appropriate and fast, assurance or trust can be seen from the safety and comfort of the community in providing services, this means that socialization regarding KIA to the community has been conveyed well.